Controllable Synthesis and Characterization of Silver Nanoparticles Using Sargassum Angostifolium - Maryam Ghaemi; Sara Gholamipour (Iranian Journal of Chemistry & Chemical Engineering, 2017)
A simple, fast and one-pot synthesis procedure based on the bioreduction ability of an algal extract solution has been developed to produce silver nanoparticles (AgNPs). We focus especially on the influencing factors of AgNPs formation. The effects of various factors like pH, temperature, the concentration of metal ions and alga, the volume ratio of silver nitrate solution to alga extract, reaction time, mixing order and the mixing rate of the silver nitrate and the alga extract on the AgNPs synthesis are evaluated. The obtained colloids have been characterized by UV–Vis spectroscopy, TEM, XRD, and FT-IR. TEM image of the silver colloids shows that the AgNPs are predominantly spherical around average particle diameters of 32±10 nm. FT-IR study indicates that the carboxyl (−C=O), hydroxyl (−OH), and amine (N–H) groups in alga extract are mainly involved in the reduction of Ag+ ions to AgNPs. The XRD spectrum clearly shows that the AgNPs are crystalline in nature. This work may prove to be of great value in synthesizing nanoparticles with well-controlled sizes in chemical, pharmaceutical, and materials production processes.